GPRS-BASED REMOTE SENSING AND CLIMATE CONTROL SYSTEM USING CMOD CPLD - El-Medany, Wael M. (International Journal of Computing, 2014)
This paper presents the design and VLSI hardware implementation of a remote sensing system for humidity and temperature in real time. The remote monitoring of the system based on a web design by using GPRS (General Packet Radio Service) network. Since full custom ASIC design takes long time with high cost, programmable logic devices as a programmable ASIC is a better choice for rapid design process and reasonable prices. The design has been described using VHDL (VHSIC Hardware Description Language), and then implemented in hardware using CoolRunner2 CPLD from Xilinx to achieve low cost with rapid prototyping. The design has been simulated and synthesized using Xilinx ISE 6.2i software tools, then test in hardware level using Digilent Spartan 3 starter kit as a hardware tools. The design offers a complete, low cost, powerful and user friendly way of 24 hours real time monitoring system.